Pd‐Catalyzed MIA‐Directed Acetoxylation of Benzylamines and Computational Study - Meng, Yue‐Ning; Zhao, Shi‐Chen; Liu, Peng‐Yu; Hu, Dianwen; Wang, Shuai; He, Yu‐Peng; Yu, Fang (European journal of organic chemistry, 2022)
The direct acetoxylation of substituted benzylamines has been accomplished through methoxyiminoacyl (MIA)‐mediated Pd‐catalyzed C−H functionalization. A diverse array of phenylalanine substrates is amenable to this protocol, providing acetoxylation benzylamine derivatives with good to high efficiency. Computational results revealed that HOAc enhanced the stability of Pd−O bond, which obviously accelerate the reductive elimination step of the acetoxylation process. A highly efficient MIA‐mediated acetoxylation of substituted benzylamines was reported, which tolerate various substituent groups with good to high yields. DFT‐Studies showed that a weaker electrostatic attraction of HOAc to OAc led to the preferential formation of a five‐membered cyclopalladium intermediate (OAc−Pd−C).